Genetic Factors Influencing Sperm Competition - Civetta, Alberto; Ranz, José M. (Frontiers in Genetics, 2019)
Females of many different species often mate with multiple males, creating opportunities for competition among their sperm. Although originally unappreciated, sperm competition is now considered a central form of post-copulatory male-male competition that biases fertilization. Assays of differences in sperm competitive ability between males, and interactions between females and males, have made it possible to infer some of the main mechanism of sperm competition. Nevertheless, classical genetic approaches have encountered difficulties in identifying loci influencing sperm competitiveness while functional and comparative genomic methodologies, as well as genetic variant association studies, have uncovered some interesting candidate genes. We highlight how the systematic implementation of approaches that incorporate gene perturbation assays in experimental competitive settings, together with the monitoring of progeny output or sperm features and behavior, has allowed the identification of genes unambiguously linked to sperm competitiveness. The emerging portrait from 38 genes is their remarkable breadth of biological roles exerted through males and females, the non-preponderance of sperm genes, and their overall pleiotropic nature.